2002
DOI: 10.1016/s0893-133x(01)00309-8
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine-Induced Dopamine Release and Post-Synaptic Specific Binding in Patients with Mild Tardive Dyskinesia

Abstract: Several lines of evidence suggest that changes in dopamine release and/or post-synaptic sensitivity may be involved in the pathogenesis of tardive dyskinesia (TD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Direct evidence for this hypothesis in humans is not as strong. Whereas chronic antipsychotic use has been shown to increase striatal D2‐receptor binding on PET imaging with a possible association with TD,33 larger studies have not shown this change to be correlated with severity of dyskinesia 34–36. Also, postmortem studies have not shown significant differences in D2‐receptor numbers between patients with and without tardive movement disorders,37 implying that D2‐receptor hypersensitivity may result from chronic antipsychotic use, but that TD does not always result.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Direct evidence for this hypothesis in humans is not as strong. Whereas chronic antipsychotic use has been shown to increase striatal D2‐receptor binding on PET imaging with a possible association with TD,33 larger studies have not shown this change to be correlated with severity of dyskinesia 34–36. Also, postmortem studies have not shown significant differences in D2‐receptor numbers between patients with and without tardive movement disorders,37 implying that D2‐receptor hypersensitivity may result from chronic antipsychotic use, but that TD does not always result.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In vitro theory on competition between endogenous ligand, i.e., acetylcholine in the present study, and radioligand indicates that the binding of the latter should be affected by the concentration of the former. This competition has been demonstrated in vivo using positron emission tomography (PET) for the dopaminergic system and the D2 antagonist [ 11 C]raclopride (Adler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it should be noted that D 2 supersensitivity does not always follow long-term administration of antipsychotic drugs. [7][8][9][10][11]20 The effects of previous antipsychotic drug treatment in subjects with schizophrenia may be a confounding factor and limitation to the study. Although all drugs were withdrawn at least 1 week prior to the study, this may have not been enough time to exclude persisting effects of antipsychotics on the brain.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, this is not consistently reported, and some investigators have found no significant association between the D 2 system and TD. [7][8][9][10][11] Methodological issues have contributed to these reported differences. First, medication effects relating to the evaluation of TD are a primary consideration.…”
mentioning
confidence: 99%